Well-Being and Arthritis Incidence: The Role of Inflammatory Mechanisms. Findings From the English Longitudinal Study of Ageing - Okely, Judith A. (Psychosom Med, 2017)
OBJECTIVE: Higher levels of well-being are associated with lower levels of inflammatory markers in healthy populations; however, it is unclear whether this association translates into a reduced risk of disease. In the current study, we tested whether the association between well-being and inflammation results in a lower risk of arthritis. METHODS: The sample consisted of 5622 participants 50 years or older from the English Longitudinal Study of Ageing and included six waves of data collection. We used a structural equation modeling approach to test whether inflammatory markers (C-reactive protein [CRP] or fibrinogen) mediated the association between well-being and arthritis risk for a 10-year follow-up period. RESULTS: Higher levels of well-being were associated with a decrease in arthritis risk (hazard ratio = 0.97 per unit, 95% confidence interval = 0.96 to 0.98, p < .001). Of the two inflammatory markers, only CRP was associated with arthritis risk. Mediation analysis revealed that the indirect effect of well-being (at wave 1) on arthritis risk via CRP (at wave 2) was significant (hazard ratio = 0.996, 95% confidence interval = 0.995 to 0.998, p < .001). This effect remained significant after adjustment for demographic and health behavior variables and depressive symptoms. CONCLUSIONS: CRP accounts for a small proportion of the association between well-being and a reduced risk of arthritis.